2018
DOI: 10.1115/1.4040208
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Discrete Second-Order Sliding Mode Control With Application to Nonlinear Automotive Systems

Abstract: Sliding mode control (SMC) is a robust and computationally efficient model-based controller design technique for highly nonlinear systems, in the presence of model and external uncertainties. However, the implementation of the conventional continuous-time SMC on digital computers is limited, due to the imprecisions caused by data sampling and quantization, and the chattering phenomena, which results in high frequency oscillations. One effective solution to minimize the effects of data sampling and quantization… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Several works on hybrid combination of various SMC and disturbance observer have been addressed for effective robustness, reduce chattering and finite time stability with the mismatched disturbances (Charfeddine and Lassaad, 2015). These SMC with disturbance observer or GS with sliding mode disturbance observer or by adaptive and fuzzy based have been implemented to varied electrical processes like permanent magnet linear model, semi-automated hand-held ear surgical device and attitude control for the dual arm of a humanoid robot (Amini et al, 2018; Charfeddine and Lassaad, 2015; Sinha and Mishra, 2018). But not much concentration was given to noise and matched disturbances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several works on hybrid combination of various SMC and disturbance observer have been addressed for effective robustness, reduce chattering and finite time stability with the mismatched disturbances (Charfeddine and Lassaad, 2015). These SMC with disturbance observer or GS with sliding mode disturbance observer or by adaptive and fuzzy based have been implemented to varied electrical processes like permanent magnet linear model, semi-automated hand-held ear surgical device and attitude control for the dual arm of a humanoid robot (Amini et al, 2018; Charfeddine and Lassaad, 2015; Sinha and Mishra, 2018). But not much concentration was given to noise and matched disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…Sinha and Mishra (2018) presented event-driven SMC which ensures closed-loop stability to control temperature and concentration. Amini et al (2018) explained an adaptive second-order discrete SMC (DSMC), and it shows that the tracking performance can be improved up to 90% while comparing with first-order DSMC. However, most of the above techniques show undesirable non-minimum phase and overshoot.…”
Section: Introductionmentioning
confidence: 99%
“…Salgado et al (2016) suggested a super-twisting-like discrete SMC and demonstrated its convergence to an ultimate finite bound. A discrete adaptive 2SMC based on Lyapunov stability for an uncertain non-linear combustion engine is studied by Amini et al (2018). Sharma and Janardhanan (2018) developed a higher order SMC with a disturbance forecast strategy for discrete linear uncertain system.…”
Section: Introductionmentioning
confidence: 99%
“…This approach reduces the computational load in comparison to traditional SMC. Amini et al proposed an adaptive second order Discrete Sliding Mode Control (DSMC), and results showed that the tracking performance can be improved up to 90% in comparison to first order DSMC. However, the overall improvement is 25% when shifted from single‐input single‐output to multi‐input multi‐output system.…”
Section: Introductionmentioning
confidence: 99%